Повышение эффективности использования производственных фондов в условиях кризисной ситуации - Смоловик, Раиса Федоровна; Коротун, Оксана Владимировна (Технологический центр, 2009)
In the article different approaches are analysed to determination and maintenance of process of turnover of cost of funds of productions on enterprises.
Keywords: рентабельность; объем продукции; фондоотдача; себестоимость